КАРАКАЛПАКСКИЕ СВАДЕБНЫЕ ПЕСНИ «СЫҢСЫЎ» В КОНТЕКСТЕ ОБРЯДОВ - Бекжанова, Б. (SCIENCE and SOCIETY, 2019)
Karakalpak wedding-ritual folklore has an important historical ethnographic meaning in the study of the history of the Karakalpak people. The article is devoted to the analysis of wedding-ritual songs “Singsiw” from historical-ethnographic points of view, that are performed in seeing off with a girl before marriage. “Singsiw” is not only one of the genres of wedding-ritual songs, but it is considered to be as a national wedding custom-ritual used for seeing off with a girl to her bride-groom’s house. The author of the article defined the historical-genetic origin of songs, and ways of their transformation at different periods of social development, and also national and historical-ethnographic peculiarities of wedding-ritual songs “Singsiw”.